De Limburger J.H. Bormans als Neerlandicus - Vanderheyden, Jan F. (Gent : Erasmus, 1955)
Bibliotheek Camille Huysmans
Dedicator: Vanderheyden, Jan F., dedicatee: Huysmans, Camille
Nederlands
Brochure
Keywords: letterkunde; Limburg